Preparation and Thermal Degradation of White Fluorinated Polyimide/TiO2 Composite Films with Strong Shielding Performance. Issue 2 (22nd January 2019) - Li, Linshuang; Xu, Yong; Che, Jianfei; Xiaohong, Liu; Zhao, Wei; Ye, Zhifeng
ABSTRACT: A series of white fluorinated polyimide/TiO2 composite films were prepared by a solution mixing method. They showed high tensile strength beyond 95.1MPa and excellent insulting property with surface and volume resistances exceeding 1.9 × 10 11 Ω and 2.3 × 10 12  Ω cm, respectively, coupled with water absorptions below 1.1%, water contact angles up to 95.9 and whiteness beyond 58.5. It was found that their optical transparency decreased dramatically with the increasing doping of TiO2 . The thermal degradation of pure fluorinated polyimide (FPI) and representative polyimide/TiO2 composite film with 5 wt% of TiO2 (PI/TiO2 -5 wt%) was also studied. GRAPHICAL ABSTRACT: GRAPHICAL ABSTRACT